Urine scent marking (USM): a novel test for depressive-like behavior and a predictor of stress resiliency in mice. - Michael L Lehmann; Claire E Geddes; Jennifer L Lee; Miles Herkenham (PLoS ONE, 2013)
Decreased interest in pleasurable stimuli including social withdrawal and reduced libido are some of the key symptomatic criteria for major depression, and thus assays that measure social and sexual behavior in rodents may be highly appropriate for modeling depressive states. Here we present a novel approach for validating rodent models of depression by assessing male urine scent marking (USM) made in consequence to a spot of urine from a proestrous female. USM is an ethologically important form of sexual communication expressed by males to attract females. The expression of this behavior is highly sensitive and adaptive to environmental cues and social status. We hypothesized that male USM behavior offers a naturalistic measure of social motivation that can be used to evaluate hedonic behaviors relevant to the study of mood disorders. We demonstrated that 1) adult male mice displayed a strong preference for marking proestrous female urine with a high degree of specificity, 2) exposure to chronic social defeat profoundly decreased USM whereas exposure to environmental enrichment increased USM, 3) the standard antidepressant fluoxetine reversed declines in USM induced by social defeat, 4) USM behavior closely correlated with other hedonic measures, and 5) USM scores in non-stressed mice predicted behavioral outcomes after defeat exposure such that mice displaying high preference for marking female urine prior to social defeat showed behavioral resiliency after social defeat. The findings indicate that the USM test is a sensitive, validated measure of psychosocial stress effects that has high predictive value for examination of stress resiliency and vulnerability and their neurobiological substrates.